The Effects of Gender and Parental Occupation in the Apprenticeship Market : an Experimental Evaluation - Fernandes, Ana [Verfasser]; Huber, Martin [Verfasser]; Plaza, Camila [Verfasser] (My University, 2019)
"This study investigates the effects of applicant gender and parental occupation on callback rates in the Swiss apprenticeship market, i.e. invitations to an interview or trial apprenticeship. It sheds light on the question of whether employer behaviour in terms of callbacks contributes to occupational segregation, i.e. differences in occupational choices across gender and socio-economic status, when considering the earliest point of entry into the labor market. We ran a correspondence test and sent out fictitious job applications with randomized gender and parental occupation to apprenticeship vacancies in several Swiss regions. We generally find no robust evidence for a differential treatment by employers, as gender and parental occupation do not statistically signifcantly aspect callback rates in most cases. The one exception is stating father's occupation to be university professor, which statistically significantly boots call backs for female applications even when accounting for multiple hypothesis testing, but not for male applications. This suggests that applications should ideally not reveal socio-economic information." (authors' abstract; BIBB-Doku)

Mit geschlechterspezifischer Diskriminierung auf dem Lehrstellenmarkt beschäftigt sich eine Studie der Universitäten Bern, Basel und Fribourg. Ein Forschungsteam hat fiktive Bewerbungsschreiben von Jugendlichen auf Lehrstellensuche verschickt, in Basel, Bern, Zürich und Lausanne. Nebst dem Einfluss des Geschlechts im Selektionsprozess interessierte die Forschenden auch, ob der Beruf der Eltern im Selektionsprozess eine Rolle spielt. Die ausgewerteten Daten zeigen: Auf dem Lehrstellenmarkt lässt sich keine geschlechterspezifische Diskriminierung feststellen. Auch der Berufshintergrund der Eltern spielt kaum eine Rolle - mit einer Ausnahme, dass Mädchen, die einen Professor als Vater haben, die Rockstars bei der Lehrstellensuche seien. Ihre Chance, zu einem Bewerbungsgespräch eingeladen zu werden, erhöht sich um 20 Prozent. (BIBB-Doku)
Keywords: G 2.4.5 Gender Mainstreaming; I 2.2.1 Westeuropa; Ausbildungsstellenmarkt; Bewerbung; Ausbildungschance; Geschlecht; Geschlechtersegregation; Eltern; Beruf; Beruflicher Status; Einflussfaktor; Schweiz